Relationship commitment and alcohol use consequences among sexual minority women. Issue 4 (1st October 2020) - Mendoza, Natasha S.; Borders, Jessica; Sherman, Athena D. F.; Thomas, DeShay; Harner, Vern; Cimino, Andrea
Abstract: Sexual minority women [SMW] are a considerable population, yet they are often overlooked in behavioral health research focused on problematic alcohol use. With a foundation in Relational-Cultural Theory, we examined the association between relationship commitment and alcohol-related consequences among SMW. Participants were recruited to take part in a study about behavioral health and relationship functioning. Analyses included multiple regression. Preliminary findings indicated that commitment is associated with adverse alcohol use consequences among SMW in relationships. There is a need for more research examining the role of substance use in the context of committed same-gender relationships. Clinical practitioners who work with SMW couples should explore substance use patterns and associated consequences to better target the needs of SMW in committed relationships.